The New Digital Age Reshaping the Future of People, Nations and Business
THE NEW DIGITAL AGE is the product of an unparalleled collaboration: full of the brilliant insights of one of Silicon Valley\'s great innovators - what Bill Gates was to Microsoft and Steve Jobs was to Apple, Schmidt (along with Larry Page and Sergey Brin) was to Google - and the Director of Google Ideas, Jared Cohen, formerly an advisor to both Secretaries of State Condoleezza Rice and Hillary Clinton.Never before has the future been so vividly and transparently imagined. From technologies that will change lives (information systems that greatly increase productivity, safety and our quality of life, thought-controlled motion technology that can revolutionise medical procedures, and near-perfect translation technology that allows us to have more diversified interactions) to our most important future considerations (curating our online identity and fighting those who would do harm with it) to the widespread political change that will transform the globe (through transformations in conflict, increasingly active and global citizenries, a new wave of cyber-terrorism and states operating simultaneously in the physical and virtual realms) to the ever present threats to our privacy and security, Schmidt and Cohen outline in great detail and scope all the promise and peril awaiting us in the coming decades. A breakthrough book - pragmatic, inspirational and totally fascinating. Whether a government, a business or an individual, we must understand technology if we want to understand the future.